Free space optical networks for ultra-broad band services - Kartalopoulos, Stamatios V. (Hoboken, N.J. : Wiley ; Piscataway, NJ : IEEE Press, 2011)
"Free Space Optical Network is a next generation communication network which uses optical waves instead of microwaves, potentially offering faster communication with ultra band width, meaning more complex communication services can be simultaneously offered. This book describes the network concepts in simple language starting with point-to-point free space optics basics and discusses networking, interoperability with existing communication network, and security. An ideal resource for communication professionals just entering the free space optical communication field and graduate students majoring in optical communications"--Provided by publisher.
1 Propagation Of Light In Unguided Media -- 1.1 Introduction -- 1.2 Laser Beam Characteristics -- 1.2.1 Wavelength -- 1.2.2 Beam Profile and Modes -- 1.2.3 Beam Divergence -- 1.2.4 Rayleigh Range -- 1.2.5 Near-Field and Far-Field Distribution -- 1.2.6 Peak Wavelength -- 1.2.7 Degree of Coherence -- 1.2.8 Photometric Terms -- 1.2.9 Radiometric Terms -- 1.2.10 Beam Power and Intensity -- 1.2.11 The Decibel Unit -- 1.2.12 Laser Safety -- 1.2.13 Cassification of Lasers -- 1.3 Atmospheric Layers -- 1.4 Atmospheric Effects on Optical Signals -- 1.4.1 Refractive Index of Air -- 1.4.2 Atmospheric Electricity -- 1.4.3 Atmospheric Tide -- 1.4.4 Definitions -- 1.4.4.1 Parts Per Million by Volume (PPMV) -- 1.4.4.2 Visibility -- 1.4.5 Absorption and Attenuation -- 1.4.6 Fog -- 1.4.7 Smog -- 1.4.8 Rain -- 1.4.9 Snow -- 1.4.10 Solar Interference -- 1.4.11 Scattering -- 1.4.11.1 Rayleigh Scattering -- 1.4.11.2 Mie Scattering -- 1.4.11.3 Geometric Scattering -- 1.4.12 Scintillation -- 1.4.13 Wind and Beam Wander -- 1.5 Coding for Atmospheric Optical Propagation -- 1.6 LIDAR -- 2 FSO Transceiver Design -- 2.1 Introduction -- 2.2 Light Sources -- 2.2.1 Laser Classification Based on Reach -- 2.2.2 Parameters of Laser Sources -- 2.2.3 Light Emitting Diodes -- 2.2.4 LASERs -- 2.2.4.1 Fabry-Perot Semiconductor Lasers -- 2.2.4.2 Bragg Lasers -- 2.2.4.3 VCSEL Lasers -- 2.2.4.4 Titanium-doped Sapphire Lasers -- 2.2.4.5 Laser Comparison -- 2.3 Modulators -- 2.3.1 The Amplitude Modulation -- 2.4 Photodetectors and Receivers -- 2.4.1 Cut-off Wavelength -- 2.4.2 Photodetector Parameters -- 2.4.3 The PIN Photodiode -- 2.4.4 The APD Photodiode -- 2.4.5 Photodetector Figure of Merit -- 2.4.6 Silicon and InGaAS Photodetectors -- 2.4.6.1 Silicon-based Photodetectors -- 2.4.6.2 InGaAs-based Photodetectors -- 2.4.6.3 Ge-based Photodetectors -- 2.4.6.4 Selecting a Photodetector -- 2.5 Optical Amplification -- 2.5.1 Optical Amplifier Characteristics -- 2.5.2 Semiconductor Optical Amplifiers -- 2.5.3 Optical Fiber Amplifiers -- 2.5.4 Erbium Doped Fiber Amplifiers -- 2.6 Optical Signal to Noise Ratio -- 2.6.1 Signal Quality -- 2.6.2 Signal Quality Monitoring Methods -- 2.7 Acquisition, Pointing and Tracking -- 2.7.1 Acquisition -- 2.7.2 Pointing -- 2.7.3 Tracking -- 2.7.4 Corner Cube Reflectors -- 2.8 Adaptive and Active Optics -- 2.8.1 Methods for Adaptive Optics and Active Optics -- 2.8.2 The Reference Star -- 2.9 Laser Safety -- 2.10 Node Housing and Mounting -- 3 Point-To-Point FSO Systems -- 3.1 Introduction -- 3.2 Simple PtP Design -- 3.2.1 Simple PtP Transceiver Design -- 3.2.2 Effect of Wind on LoS -- 3.2.3 Simple PtP Power Budget Estimation -- 3.2.4 Modeling Atmospheric Loss -- 3.3 Point-to-Point with Transponder Nodes -- 3.3.1 PtP Transceiver Design with Add-Drop -- 3.3.2 Power Budget for PtP with Add-Drop Nodes -- 3.4 Hybrid FSO and RF -- 3.5 FSO Point-to-Multipoint -- 3.6 FSO Point-to-Mobile -- 4 Ring FSO Systems -- 4.1 Introduction -- 4.2 Ring Topologies and Service Protection -- 4.3 Ring Nodes with Add-Drop -- 4.4 Concatenated Rings -- 4.5 Ring to Network Connectivity -- 5 Mesh FSO Systems -- 5.1 Introduction -- 5.2 FSO Nodes for Mesh Topology -- 5.2.1 Parameters Pertinent to FSO Mesh Topology -- 5.2.2 Mesh-FSO Node Design -- 5.2.3 Mesh-FSO Network Protection -- 5.2.4 Mesh-FSO Scalability -- 5.3 Hybrid Mesh-FSO with RF -- 5.4 Hybrid FSO-Fiber Networks -- 6 WDM Mesh-FSO -- 6.1 Introduction -- 6.2 Light Attributes -- 6.3 Optical Media -- 6.3.1 Homogeneous and Heterogeneous Media -- 6.3.2 Isotropy and Anisotropy -- 6.3.3 Propagation of Light in Transparent Dielectric Medium -- 6.3.3.1 Phase Velocity -- 6.3.3.2 Group Velocity -- 6.4 Interaction of Light with Matter -- 6.4.1 Reflection and Refraction -- Snell's Law -- 6.4.2 Polarization of Light and Matter -- 6.4.2.1 Polarization Vector -- 6.4.2.2 Transverse Wave -- 6.4.2.3 Circular, Elliptical and Linear Polarization -- 6.5 Medium Birefringence -- 6.6 DWDM and CWDM Optical Channels -- 6.6.1 The DWDM Grid -- 6.6.2 The CWDM Grid -- 6.7 WDM FSO Links -- 6.8 WDM Mesh FSO Networks -- 6.8.1 Mesh Network Engineering -- 6.8.2 Link Alignment -- 6.8.3 Mesh-Network Optimization -- 6.9 Service Protection in Mesh-FSO Networks -- 6.9.1 Link Degradation -- 6.9.2 Link Hard Failures -- 6.9.3 Degradation of a Cluster of Nodes -- 6.10 WDM Mesh-FSO versus EM-Wireless -- 7 Integrating Mesh-FSO With The Public Network -- 7.1 Introduction -- 7.2 The Ethernet Protocol -- 7.2.1 Gigabit Ethernet -- 7.2.2.10 Gigabit Ethernet -- 7.3 The TCP/IP Protocol -- 7.3.1 The Transmission Control Protocol -- 7.3.2 The User Datagram Protocol -- 7.3.3 The Real Time Transport Protocol -- 7.3.4 The Internet Protocol -- 7.4 The ATM Protocol -- 7.5 Wireless Protocols -- 7.5.1 Wi-Fi -- 7.5.2 WiMAX -- 7.5.3 Comparison of WiMAX with Wi-Fi -- 7.5.4 LTE -- 7.5.5 Comparison of LTE with WiMAX -- 7.6 The Next Generation SONET/SDH Protocol -- 7.6.1 The Legacy SONET/SDH -- 7.6.2 SONET Frames -- 7.6.3 Virtual Tributaries and Tributary Units -- 7.6.4 STS-N Frames -- 7.6.4.1 Concatenation -- 7.6.4.2 Scrambling -- 7.6.4.3 Maintenance -- 7.7 Next Generation SONET/SDH Networks -- 7.7.1 Next Generation Ring Networks -- 7.7.2 Next Generation Mesh Networks -- 7.7.2.1 Next Generation Mesh Networks: Protection -- 7.7.2.2 Next Generation Mesh Networks: Traffic Management -- 7.7.2.3 Next Generation Mesh Networks: Wavelength Management -- 7.7.2.4 Next Generation Mesh Networks: Network Management -- 7.7.2.5 Next Generation Mesh Networks: Service Restoration -- 7.8 Next Generation Protocols -- 7.8.1 Concatenation in NG-S -- 7.8.1.1 Contiguous Concatenation -- 7.8.1.2 Virtual Concatenation -- 7.9 The GMPLS Protocol -- 7.9.1 Before GMPLS: MPLS -- 7.9.2 The GMPLS -- 7.10 The GFP Protocol -- 7.10.1 GFP Header, Error Control and Synchronization -- 7.10.2 GFP Frame Structure -- 7.10.3 GFP-F and GFP-T Modes -- 7.11 The LCAS Protocol -- 7.12 The LAPS Protocol -- 7.13 Any Protocol over SONET/SDH -- 7.13.1 EXAMPLE 1: IP over LAPS over NG-S -- 7.13.2 EXAMPLE 2: Any Payload over LAPS over Next NG-S over WDM -- 8 FSO Network Security -- 8.1 Introduction -- 8.2 Cryptography -- 8.3 Security Levels -- 8.4 Security Layers -- 8.4.1 Security on the Information Layer -- 8.4.2 Security on the MAC/Network Layer -- 8.4.3 Security on the Link Layer -- 8.4.4 FSO-Wlan Security -- 8.5 FSO Inherent Security Features -- 8.5.1 FSO Beam Overspill -- 8.5.2 Beam Tapping -- 8.5.3 FSO Cable Tapping -- 8.6 Conclusion -- 9 FSO Specific Applications -- 9.1 Introduction -- 9.2 FSO Networks for Highway Assisted Communications -- 9.3 Mesh-FSO in Disaster Areas -- 9.4 Visual Light Communication -- 9.5 Conclusion -- References.
Includes bibliographical references and index.
Keywords: Free space optical interconnects; Broadband communication systems; SCIENCE -- Waves & Wave Mechanics; COMPUTERS -- Data Transmission Systems -- General; Broadband communication systems; Free space optical interconnects; Electronic books